2018
DOI: 10.1007/s00240-018-1056-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcutaneous electrical acupoint stimulation on postoperative analgesia after ureteroscopic lithotripsy: a randomized controlled trial

Abstract: Transcutaneous electrical acupoint stimulation (TEAS) is an effective analgesic measure. We studied the analgesic effect of TEAS by applying it alone after ureteroscopic lithotripsy, rather than applying it as a supplementary analgesic measure. Participants (n = 120) scheduled to undergo ureteroscopic holmium laser lithotripsy, were enrolled and randomly assigned into Group T (TEAS n = 60) and Group C (Control, n = 60). The participants in Group T were treated with TEAS for postoperative analgesia. TEAS were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…In the present study, TEAS in combination with low-dose opioids was selected for analgesia. The results suggested that patients in the TEAS group displayed significantly lower VAS scores at 12 and 24 h post-operation, as well as reduced consumption of PCA within 48 h post-surgery, indicating that TEAS displayed potent analgesic effects, which was consistent with a previous study (27). Therefore, TEAS might be associated with effective postoperative pain relief and lower analgesic consumption.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, TEAS in combination with low-dose opioids was selected for analgesia. The results suggested that patients in the TEAS group displayed significantly lower VAS scores at 12 and 24 h post-operation, as well as reduced consumption of PCA within 48 h post-surgery, indicating that TEAS displayed potent analgesic effects, which was consistent with a previous study (27). Therefore, TEAS might be associated with effective postoperative pain relief and lower analgesic consumption.…”
Section: Discussionsupporting
confidence: 88%
“…A constant electrical stimulation was applied for 30 min each time with a dense-and-disperse frequency of 2/100 Hz (26) via a HANS LH-202 electrical stimulator (Nanjing Jisheng Medical Technology Co., Ltd.). The optimal intensity was set to mild twitching of the surrounding muscle and individual maximum tolerance (5-10 mA for upper limbs; 10-30 mA for lower limbs) (27,28). The TEAS effect was confirmed by de qi sensation (27,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the theory of traditional Chinese medicine (TCM), acupuncture on BL23 contributes to reduce the pressure in the renal pelvis, relax the smooth muscle of the ureter, and reduce the local edema caused by ureteral stones. Our previous study suggested that TEAS on BL23 and SP9 helped to alleviate postoperative pain for patients after ureteroscopic lithotripsy [ 22 ]. In fact, inflammation response is one of the common causes for postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Laser acupuncture is defined as the stimulation of traditional acupuncture points with application of a low-intensity, nonthermal laser. Although it has been shown to be effective in treating various conditions, the mechanisms underlying its effects are not yet fully understood [25][26][27][28][29][30]. The low-power lasers used in acupoints provide light-based energy capable of producing photobiomodulation induction, which, by its turn, produces biochemical and isoelectric effects on local cells, providing an anti-inflammatory and analgesic effect.…”
Section: Introductionmentioning
confidence: 99%